Jacques Derrida's Deconstruction Interpretation of Mining Permit Policy for Religious Community Organizations in Indonesia - Yuwono, Adhimas Alifian (Jurnal Filsafat "WISDOM", 2025)
This study aims to argue that the mining permit policy for religious organizations in Indonesia, as stipulated in Government Regulation No. 25 of 2024, is an act of deconstruction in the social and public policy spheres. Deconstruction, as a radical hermeneutics coined by Jacques Derrida, rejects the existence of absolute meaning (logocentrism) that dominates the understanding of texts (reality). In this context, the study highlights how the policy dismantles the old assumption that religious community organizations are only suitable to operate in the religious sphere and do not have the capability to manage mines. The process of dismantling logocentrism is analyzed in detail through six key stages of deconstruction: (1) Difference, which emphasizes the distinction and suspension of meaning between the traditional role of religious organizations and new opportunities in the mining sector; (2) Traces, which are traces of meaning recorded in public discourse and diverse responses from various parties; (3) Dissemination, which is the spread of new meanings that allow policy interpretations to develop dynamically beyond the initial intentions of policymakers; (4) Undecidability, where the meaning of a policy cannot be decided absolutely as good or bad, but is always open to negotiation; (5) Supplement, which shows that the meaning of policy is influenced by the ever-changing social, political, and economic context; and (6) Iterability, which emphasizes the autonomy of policy texts to be continuously reinterpreted by various social actors. The research results confirm that this policy is not merely an administrative change but has shaken the old structure of meaning and opened up space for dialogue across perspectives. The study recommends that the process of evaluation and critical dialogue across perspectives be kept open so that policies can develop adaptively and inclusively in line with changing times and minimize any potential negative impacts.